Carcinoma in situ and early breast carcinoma survey of the Portuguese Senology Society on treatment in Portugal and its evolution between 1985 and 2000 - Oliveira, CF (2008)
By means of a questionnaire sent to Portuguese hospitals which diagnose and treat most female patients with breast cancer, it was intended to assess the situation regarding the treatment of carcinoma in situ and early breast cancer (T1 or T2, N0 or N1), as well as their evolution between 1985 and 2000. The hospital participation rate was 65% and a sample of 865 patients was collected, distributed by the years 1985, 1990, 1995 and 2000. It was observed that, in terms of surgery, there was an increase in conservative surgery, which was over 40% in 2000, as well as an increase in the average of excised axillary lymph nodes. Progress in the surgical approach was similar both in cancer centres and in large and university hospitals, when compared with the other surveyed hospitals. Also, no differences between these two hospital groups in disease-free survival and overall survival were found. Postoperative radiotherapy was employed in more than 90% of the patients submitted to conservative surgery and adjuvant chemotherapy was used in 39% of all the patients, while tamoxifen as adjuvant treatment was used in 58% of the patients.